Plan de negocios para la creación de una empresa productora y comercializadora de arándanos en el Cantón Latacunga - Chicaiza Chicaiza, Sandra Marina (2023)
In the present investigation, a business plan was developed for the creation of a blueberry production and marketing company in the Latacunga Canton. The business idea arises from the advantage of environmental conditions, of having a similar climate during all months that favors cultivation and harvest at any time of the year. And thus, take advantage of the market opportunity given the increase in demand for the product. This research was of a theoretical, exploratory and descriptive type with a mixed approach, that is, the qualitative and quantitative analysis was made, the market survey directed to consumers and the interview directed to suppliers and producers were used; As a result of the market study, an 80% acceptance rate was obtained with an installed capacity of 150,000.00 packages per year.